Adaptive Strategies in Entrepreneurial Ventures: Navigating Uncertainty and Market Dynamics at MSMe - Heri Erlangga; Tita Setiawati; Farid Riadi; Ida Hindarsah; Dini Riani (CV. Astina Mandiri, 2024)
This study explores the critical role of adaptive strategies in maintaining the growth and competitiveness of Micro, Small, and Medium Enterprises (MSMEs) in dynamic market environments. MSMEs significantly contribute to employment creation, innovation, and overall economic development but face unique challenges such as limited resources, market access, and vulnerability to market changes. Adaptive strategies like product diversification, digital transformation, and strategic partnerships have been found effective in enhancing MSME performance. Product diversification allows MSMEs to enter new market segments and reduce dependence on a single product line, while digital transformation improves operational efficiency and market reach. Strategic partnerships provide access to previously unavailable resources like technology and distribution networks. However, the implementation of these strategies is often hampered by financial constraints, lack of technological knowledge, and resistance to change. The study also highlights the importance of continuous learning and innovation for MSMEs to stay competitive. Continuous learning updates the knowledge and skills of MSMEs in line with industry developments, while innovation enables the development of new products or services that meet changing market needs. Case studies presented in the research demonstrate successful adoption of adaptive strategies by MSMEs to address challenges and leverage market opportunities. The findings offer practical insights for MSME owners, policymakers, and academics on the importance of adaptive strategies in navigating market uncertainties and achieving sustainable growth. The study also provides recommendations for supporting MSMEs in adopting adaptive strategies through initiatives such as training programs, digital transformation funding, and strategic partnership schemes.